2018
DOI: 10.3389/fcvm.2018.00058
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Cytoskeletal Responses to Pulsatile Flow in Heart Valve Tissue Engineering Studies

Abstract: Heart valve replacement options remain exceedingly limited for pediatric patients because they cannot accommodate somatic growth. To overcome this shortcoming, heart valve tissue engineering using human bone marrow stem cells (HBMSCs) has been considered a potential solution to the treatment of critical congenital valvular defects. The mechanical environments during in vitro culture are key regulators of progenitor cell fate. Here, we report on alterations in HBMSCs, specifically in their actin cytoskeleton an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The combination of cyclic flexure and steady flow (flex-flow) induces pulsatile and/or oscillatory flow patterns on the surfaces of TEVCs. Our work, as well as others, have shown the importance of oscillatory flow conditions on developing valve tissues (6,(8)(9)(10). However, a physiologically relevant pulsatile flow waveform may be able to induce oscillations similar to the conditions experienced in the native valve, which will mechanically condition these TEVCs.…”
Section: Introductionmentioning
confidence: 50%
“…The combination of cyclic flexure and steady flow (flex-flow) induces pulsatile and/or oscillatory flow patterns on the surfaces of TEVCs. Our work, as well as others, have shown the importance of oscillatory flow conditions on developing valve tissues (6,(8)(9)(10). However, a physiologically relevant pulsatile flow waveform may be able to induce oscillations similar to the conditions experienced in the native valve, which will mechanically condition these TEVCs.…”
Section: Introductionmentioning
confidence: 50%
“…The pressure of the fluids inside the kidneys influences the podocytes, involving cyclooxygenase-2 and prostaglandins type 2 in the mechanical response and other molecules (Akt-GSK3β-β-catenin) for correct adaptation (and shape) and kidney function [31]. The constant passage of fluids maintains the shape and function of the myocardium, stimulating the potassium channels (for correct electrical function), stimulating correct repair (through the intervention of stem cells) [32][33][34]. According to a model to understand the importance of mechanotransduction in the presence of fluids, the fluid mosaic model, highlights that the cell does not behave morphologically in unison during the passage of fluidic-mechanical information but reminds a lot of the fractal concept [35 ].…”
Section: The Image Is Taken From the Don Gnocchi Chemistry And Researmentioning
confidence: 99%
“…In addition to flex-flow conditions, our laboratory has also investigated the effects of pulsatile shear stress in comparison to non-pulsatile shear on tissue cell alignment. It is observed that bone marrow stem cells respond to pulsatile shear stress with an increased level of actin filaments and a decrease in filament length, suggesting transition from a mesenchymal to endothelial phenotype, which is a crucial process in the formation of the endothelium in tissue engineered heart valves ( 118 ).…”
Section: Vascular Vs Valvular Remodeingmentioning
confidence: 99%